FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN BIDAN TENTANG PERAWATAN TALI PUSAT MENGGUNAKAN TERAPI TOPIKAL ASI DI PUSKESMAS KOTA BANDA ACEH - Putri, Eka Nuryanda; Mauliati, Desria; Efriana, Cut; Kurniawati, Putri; Cahyani, Fara; Jasti, Fifi Feronika (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
Tetanus disease in Indonesia is a very worrying disease because tetanus neonatorum has caused the death of newborns, efforts that can be done one of them is by maintaining the umbilical cord, therefore it is very important for midwives to know about how to care for a good umbilical cord, one of which uses topical breast milk. The purpose of the study was to determine the factors associated with midwives' knowledge of umbilical cord care using topical breast milk therapy at the Banda Aceh City Health Center in 2023. This research method is analytic with a Cross Sectional approach with Purposive sampling technique with a sample size of 66 midwives. This research was conducted from May 30 to June 19, 2023 with univariate and bivariate analysis with the Chi square test. The results showed that of the 66 respondents most had sufficient knowledge as many as 24 respondents (36.4%) with a p value of 0.002 information, 0.004 tenure, 0.008 education and 0.006 age. Conclusions and suggestions there is a relationship between information, working period, education and age with knowledge about topical breast milk. It is expected for respondents to increase knowledge and motivation by digging up information about topical breast milk.